Sahara : A thousand paths into the future. - Botanova, Kateryna; Kamara, Yarri; Latimer, Quinn (Basel : Culturescapes, 2023)
MOUSSA AG ASSARID, BADI, TEWA BARNOSA, SAM BERKSON, SERGE AIMÉ COULIBALY, SOULEYMANE BACHIR DIAGNE, BINTA DIAW, MUSTAFA EL-KATTAB, RAHIMA GAMBO, HINDOU OUMAROU IBRAHIM, MONIQUE ILBOUDO, ASMAA JAMA, MARYAM KAZEEM, BENAOUDA LEBDAI, NISRINE MBARKI, ACHILLE MBEMBE, YARA MEKAWEI, RADOUAN MRIZIGA, DOROTHÉE MUNYANEZA, AMY NIANG, TEMITAYO OGUNBIYI, BEN OKRI, BEYA OTHMANI, FELWINE SARR, ESTHER SEVERI, JONAS STAAL, MOHAMED SULAIMAN, WOLE TALABI
Sahara: A Thousand Paths Into the Future is devoted to the ideas, images, poetics, politics, fictions, and movements of this vast desert and its myriad voices. Focused on the cultural productions, lines of political and aesthetic thought, and multiple epistemologies and cosmologies of the Sahara, and the accompanying Sahel, this book understands the region as both an ancient space of connection and circulation—from its northern to southern shores, its dunes and volcanic mountains, to its lusher savannahs—and as a contemporary site of exchange between strikingly singular societies and communities on all sides of the desert, that aspect of the Sahara most often imaged and imagined. If the Sahara is habitually narrated as a space of radical heat and intense light, and of barren-like emptiness, this anthology approaches the region with a decolonial lens that privileges the Saharan communities and nonhuman entities who live within all aspects of its circadian rhythms, including the constructive opacity of the desert night. (provided by publisher)
boek